THE ROLE OF AMBIDEXTROUS LEADERSHIP FOR GENERATION Z IN INDONESIAN BANKING INDUSTRY - Caroline Ruslie; Helen Yap; Venny Chrisnawati; Abdul Rohman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
As Generation Z begins to join the workforce in greater numbers, gaining a deeper understanding of their traits becomes increasingly essential. This study aims to explore the relationship between Ambidextrous Leadership (AL) and Motivation (M) in influencing Employee Performance (EP), with Employee Satisfaction (ES) examined as a potential mediating variable, specifically among Gen Z employees in Indonesia's banking sector. A total of 307 Gen Z employees from prominent banks across Indonesia participated in the study, selected through purposive judgment sampling. The data was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Findings revealed that both AL and M significantly influenced ES and EP directly. However, ES did not significantly affect EP, nor did it mediate the relationships between AL and EP or M and EP. The findings highlight the need for an integrated strategy to enhance EP, focusing on strengthening ambidextrous leadership and boosting motivation. Leaders should embody an ambidextrous mindset, being adaptable, innovative, willing to take calculated risks, and attentive to performance outcomes. To improve motivation, companies should cultivate a supportive workplace culture, conduct routine performance assessments, and provide transparent career development opportunities. Companies should form ambidextrous leadership by conducting training and development, developing a flexible mindset, implementing a balanced reward system, honing communication skills and managing conflict effectively.